PENGEMBANGAN VIDEO TUTORIAL SUB MATERI PERAN TUMBUHAN DI BIDANG EKONOMI UNTUK PRAKTIKUM PEMBUATAN SEMPRONG PISANG - Syarifah, Syarifah; Daningsih, Entin; Yokhebed, Yokhebed (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aimed to know feasibility of a tutorial video for laboratory work of making banana semprong on the sub material plant role in economy and students’ responses to tutorial video. This research was Research and Development (R & D) consisting of six stages out of ten stages, namely potential and problems, data collection, product design, design validation, design revision and limited product trial. To find out the feasibility of the tutorial video, evaluation was carried out by six validators consisting of three media expert and three material experts. Aspects measured by media expert were visual communication, sound display (audio), software engineering and tutorial video characteristics while aspects measured by material experts were material substance,concept breadth, learning and linguistic aspects used. The validation was analyzed using Ratio Total Validation (RTV). Validation results showed the RTV value for material expert and media expert was 3.71 and 3.64, subsequently. Therefore both expert categorized tutorial video feasible to be used as learning media. In addition, limited product trial showed students responses was very high (81,8%). Keywords: Banana Semprong, Feasibility, R&D Method, Response, Tutorial Video